Financial Strain, Employment, and Role Captivity and Overload Over Time Among Dementia Family Caregivers. (19th July 2019) - Liu, Yin; Dokos, Malinda; Fauth, Elizabeth B; Lee, Yoon G; Zarit, Steven H
Abstract: Background and Objectives: This study examined how financial strain and changes in employment status affect subjective stressors over 12 months in 184 family caregivers of individuals with dementia. Research Design and Methods: Subjective stressors of role overload and role captivity, and employment status were measured at baseline, 6-, and 12-months. Self-reports on financial strain were measured at baseline only. Caregivers were categorized into 3 groups based on changes in their employment status during the study over 12 months: (a) who were never employed, (b) who experienced some sort of employment status change, either going from employment to unemployment or vice versa, and (c) who were always employed. Growth curve analyses were conducted to examine within-person changes in role overload and role captivity, and associations with employment and financial strain. Results: Caregivers with greater financial strain at baseline had higher levels of role overload and increasing role captivity over time. Caregivers who experienced a caregiving transition and had low financial strain at baseline showed greater decrease in role captivity over 12 months. Although caregivers who were consistently unemployed reported lower levels of role overload, they also showed steeper increase over time than those who were consistently employed. Discussion and Implications: Caregivers' perceptions of financial strain add to the long-term stress of the caregiving role. Changes in caregivers' employment status may have complex associations with their feelings of stress over time.